(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Written speech is of great importance in the formation of children’s mental development and scientific outlook. Only a student who has a rich mindset and can think logically can quickly master modern skills and express his thoughts simply and concisely. For this purpose, one of the urgent tasks is to develop children’s written speech in the classes of primary school mother tongue classes. The article reveals the characteristics of the written speech of elementary school students. The author proved his ideas by quoting the opinions of scientists.